Comparative effect of nutraceuticals on lipid profile: a protocol for systematic review and network meta-analysis. Issue 8 (20th August 2020) - Morze, Jakub; Osadnik, Tadeusz; Osadnik, Kamila; Lejawa, Mateusz; Jakubiak, Grzegorz; Pawlas, Natalia; Gasior, Mariusz; Schwingshackl, Lukas; Banach, Maciej
Abstract : Introduction: According to the common definition, nutraceuticals are components found in food that can act as therapeutic substances. Recently, the International Lipid Expert Panel published two position papers covering the topic of lipid-lowering nutraceuticals and their potential use as a complementary treatment in addition to statins or as an alternative treatment in statin-intolerant patients. The aim of this study was to compare the effect of different nutraceuticals on lipid profiles in a systematic review with pairwise and network meta-analyses. Methods and analysis: Three databases, including PubMed, Embase and the Cochrane Central Register of Controlled Trials, will be searched without time or publication language restrictions. The estimated end date for the searches will be 29 March 2020. Each stage of the review, including the study section, data extraction, and risk of bias and quality of evidence assessments, will be performed in duplicate. Randomised controlled trials meeting the following criteria will be eligible for inclusion: (1) participants aged ≥18 years, (2) intervention with a selected nutraceutical (artichoke, berberine, bergamot, soluble fibres, green tea, garlic, lupin, plant sterols and stanols, red yeast rice, soybean, spirulina or a combination of the aforementioned nutraceuticals), (3) administration of the treatment in the form of capsules, pills, powders, solutions, tablets or enriched food items, (4) comparison with another nutraceutical or placebo, (5) intervention period ≥3 weeks and (6) lipid profile (low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, total cholesterol, triglycerides) as an outcome. Random-effect pairwise and network meta-analyses will be used to summarise the relative effect of each nutraceutical in comparison to the effect of every other nutraceutical. Subgroup analyses will be stratified by age, sex, ethnicity, sample size, length of trial follow-up, baseline cholesterol level and presence of other comorbidities. Ethics and dissemination: This review will summarise findings from primary studies, and therefore no ethics approval is required. The results will be presented at conferences as well as published in a peer-reviewed journal. PROSPERO registration number: CRD42019132877.